Determining the factors affecting consumer’s purchase intention towards foreign brands among the y-generation in the northern area of Malaysia / Etty Harniza Harun, Mahazir Ismail, Nur Aizureen Anwar - Harun, Etty Harniza; Ismail, Mahazir; Anwar, Nur Aizureen (Institute of Research Management & Innovation (IRMI), 2014)
Marketers in the developing nation is now facing with greater challenge as they have to compete with marketers from outside their home country in attracting consumers to buy their product. Having to look at the current scenario in Malaysia, efforts has been made to survey and compare the number of local brands and foreign brands available in many shopping complexes and it is found out that the majority of the brand names is not locally made. Therefore, the objective of this study is to determine the factors of Purchase Intention towards foreign brands in Malaysia among the Gen Y. There are three factors said to have effect the Gen Y’s purchase intention that is Perceived Quality, Perceived Prestige and Influence of others in two categories namely personal care and apparel. From the result, it was found that the factor of perceiving product to have a higher prestige does give effect in the purchase intention of students to buy personal care and apparel. In addition, perceived quality for personal care does not give effect to the buyers from Gen Y category in increasing their intention to purchase. Meaning that, they did not emphasize on quality when buying personal care item. Unlike apparel, the Gen Y emphasize on the quality factor in moving towards their intention to purchase an item. As for the third factor that is influence of others, the result found that influence of others does not give effect to them in purchasing foreign item for personal care and apparel. This means that, when purchasing apparel and personal care items, influence of others does not contribute m influencing them to buy foreign or local brand item.